Determinants of Company Performance: An Analysis of Corporate Culture, Human Resource Quality, Leadership and Information Technology - Liana, Esti; Ratnawati, Kusuma (Dinasti Publisher, 2024)
The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of human resource management. The literature review research article determines company performance: analysis of corporate culture, human resource quality, leadership and information technology which is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Corporate Culture affects Company Performance; 2) Quality of Human Resources affects Company Performance; 3) Leadership affects Company Performance; and 4) Information Technology affects Company Performance.